Islamic empires : the cities that shaped civilization : from Mecca to Dubai - Marozzi, Justin, 1970- (New York : Pegasus Books, 2020)
A history of the rich and diverse civilizations over fifteen centuries of Islam seen through its greatest cities.
List of illustrations -- List of maps -- A note on spelling -- Preface -- 1. 7th century: Mecca -- mother of all cities -- 2. 8th century: Damascus -- the perfumed paradise -- 3. 9th century: Baghdad -- city of peace, city of blood -- 4. 10th century: Cordoba -- ornament of the world -- 5. 11th century: Jerusalem -- the contested city -- 6. 12th century: Cairo -- the city victorious -- 7. 13th century: Fez -- the Athens of Africa -- 8. 14th century: Samarkand -- garden of the soul -- 9. 15th century: Constantinople -- city of the world's desire -- 10. 16th century: Kabul -- a garden in the mountains -- 11. 17th century: Isfahan -- half the world -- 12. 18th century: Tripoli -- pirates' lair -- 13. 19th century: Beirut -- playground of the Levant -- 14. 20th century: Dubai -- build it and they will come -- 15. 21st century: Doha -- city of pearls -- Notes -- Bibliography -- Acknowledgments -- Index.
Includes bibliographical references (pages 404-420) and index.
Buku bacaan asas siswazah Fakulti Pengajian Islam.
Keywords: Islamic civilization; Cities and towns -- Islamic Empire -- History; Islamic Empire -- History; Islam -- History; Villes -- Empire islamique -- Histoire; Islam -- Histoire